Teacher’s Recruitment, Salaries, and Development: Equity and Quality issues in Eklavya Model Residential Schools - Karmakar, Dipak (Voices of Teachers and Teacher Educators, 2022)
Eklavya Model Residential Schools (EMRS) are a scheme for establishing schools in tribal pockets across the country to provide quality education for Scheduled Tribes (STs). The present study focused on the necessity of qualified regular teacher recruitment across EMRSs concerning equitable quality education for tribal children. It also intends to explore the current status of teacher recruitment concerning qualification, salary structure, and responsibilities. The study revealed that massive contractual teacher deployment affects the quality of schooling concerning equity parameters compared with other Govt. Schools. The study also validates that contractual recruitment of teachers limits their responsibility. Therefore, a sense of belongingness and teacher leadership beyond the classroom is lacking in these schools. Thus, in a nutshell, it questions equitable quality education for tribal children in terms of teacher recruitment policy, as skilfully qualified teachers are the prime resources for quality schooling.